Framing the science for technical measures used in regulatory frameworks to effectively implement government policy - Cormier, Roland; Tunney, Tyler; Mallet, Manon (Frontiers in Marine Science, 2022)
Regulatory and non-regulatory frameworks are used extensively to establish standards and guidelines for the technical measures implemented to manage freshwater and marine activities to achieve environmental policy objectives. Scientific and technical knowledge about the effectiveness of such measures is needed to ensure the success of these objectives, and yet there is general lack of scientific information on the effectiveness of technical measures. Used as conditions of approval for a variety of industry sectors, regulations and environmental quality guidelines establish the outcomes that are expected for the technical measures used in the daily activities of a given worksite. This paper suggests that the science to determine the effectiveness of technical measures should be framed from the requirements established in regulations and environmental quality guidelines. Such studies should also use methods, indicators and metrics that are often part of those requirements. This paper also puts forth that a more focused scientific effort is needed to determine the effectiveness of technical measures given the thousands of technical measures used to manage a wide range of activities.